Fatigue crack characterisation in 2024-T351 aluminium alloy through SEM observation combined with the CJP model - Robles, J.M.; Vasco-Olmo, J.M.; Cruces, A.S.; Díaz, Francisco A.; James, Neil; López-Crespo, Pablo (Elsevier, 2023)
This work characterises crack growth in AA2024-T315 by combining different methods to further increase the reliability of the results. The Christopher-James-Patterson (CJP) model was fitted to experimental data obtained by digital image correlation (DIC). The effective value of the CJP stress intensity factors were successfully correlated with the ΔK-da/dN curve as obtained with Scanning Electron Microscopy measurements of the depth of striations on the fracture surface. This approach based on fitting the CJP model with DIC data and SEM observations allowed estimation of opening and closure loads and allowed the propagation rate and fracture mode to be effectively characterised.
Keywords: Procesado de imágenes -- Técnicas digitales; Fatigue crack growth; CJP model; Digital Image; Correlation; Scanning Electron Microscopy